Pengaruh Pelaporan Pengusaha Kena Pajak, Pemeriksaan Pajak Dan Surat Tagihan Pajak Terhadap Penerimaan Pajak Pertambahan Nilai Pada Kpp Pratama Serang Tahun 2014-2017 - Irul Meidhawati; Andi Andi; Denny Susanto (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to examine the Effects of Reporting of Taxable Entrepreneurs, Tax Examinations and Letter of Tax Liability Against Value Added Tax Receipts. This type of research is quantitative research. the type of data used is secondary data. The population in this study is an annual report consisting of: Reports on the number of submissions of VAT Announcements, SKPKB Reports, Tax Billing Letter Reports and Reports on the amount of value added tax receipts at the Serang Tax Office. The sample taken in this study is monthly data during the period January - December from 2014-2017, which is as many as 48 samples, after the data was collected, the data were analyzed using SPSS 23.The purpose of this study is to determine whether: 1) Taxable Entrepreneur Reporting affects the value added tax receipts. 2) Tax Examination has an effect on Value Added Tax Receipts. 3) Tax Collection Letter influences the receipt of Value Added Tax.The results of this study are as follows: (1) Amount of Reporting of Income Tax Entrepreneurs is significant to VAT receipts. (2) Tax Examination approves significantly on VAT receipts. (3) Letter of Tax Collection significant acceptance of VAT receipts.This study aims to examine the Effects of Reporting of Taxable Entrepreneurs, Tax Examinations and Letter of Tax Liability Against Value Added Tax Receipts. This type of research is quantitative research. the type of data used is secondary data. The population in this study is an annual report consisting of: Reports on the number of submissions of VAT Announcements, SKPKB Reports, Tax Billing Letter Reports and Reports on the amount of value added tax receipts at the Serang Tax Office. The sample taken in this study is monthly data during the period January - December from 2014-2017, which is as many as 48 samples, after the data was collected, the data were analyzed using SPSS 23.The purpose of this study is to determine whether: 1) Taxable Entrepreneur Reporting affects the value added tax receipts. 2) Tax Examination has an effect on Value Added Tax Receipts. 3) Tax Collection Letter influences the receipt of Value Added Tax.The results of this study are as follows: (1) Amount of Reporting of Income Tax Entrepreneurs is significant to VAT receipts. (2) Tax Examination approves significantly on VAT receipts. (3) Letter of Tax Collection significant acceptance of VAT receipts.